DOES SYSTEMIC FUNCTIONAL LINGUISTICS GENRE PEDAGOGY FACILITATE ISLAMIC SCHOOL STUDENTS' WRITING? - Fazri Nur Yusuf; Oti Rofiawati (Indonesian EFL Journal)
This study aimed at investigating how systemic functional linguistics genre pedagogy facilitates Islamic school students' writing exposition text. Grounded in qualitative approach, this study was in a case study employing three instruments; written documents, classroom observations, and interviews. Results revealed systemic functional linguistic genre pedagogy facilitated and enhanced students' exposition text writing on context, discourse, grammar, and graphical features. Compared to their diagnostic writing, the students could develop their first draft to the final draft through constructing genre-based schematic structures and using a more comprehensive range of lexico-grammatical resources. The enhancement between the diagnostic writing and final draft were indicated by the knowledge of the topic written, the knowledge of the exposition writing including the stages, phases, vocabularies, and grammar aspects. Along with the teachers' step-by-step guidance, the students were engaged in individual writing, their writing progress was demonstrated throughout the teaching and learning activities where students seemed to be more motivated and engaged and could grasp meaningful knowledge better. This also supported their writing in the final draft of their written works. Results also indicated that the teaching and learning processes, from building knowledge to independent construction, were all crucial to facilitate the Islamic secondary school students to improve their knowledge of writing and the writing product. It recommends that these stages can help students gain a deep understanding of the holistic concept of exposition text writing.